PENATALAKSANAAN NYERI AKUT PADA PASIEN HERNIA DENGAN INTERVENSI RELAKSASI NAPAS DALAM - Windarti; julfilkar Adnan Irnu (Politeknik Karya Husada, 2025)
Background: Hernia is a medical condition in which part of an internal organ, especially the intestine, protrudes through a weakened section of the abdominal wall. The primary treatment is surgery; however, postoperative recovery is often accompanied by acute pain, which can hinder the healing process. One safe and simple non-pharmacological intervention is deep breathing relaxation therapy. Objective: This study aims to determine the management of two patients with hernia whose primary problem was acute pain, and to evaluate the effectiveness of deep breathing relaxation therapy in reducing pain intensity. Methods: This research employed an explanatory case study design by implementing Evidence-Based Practice (EBP). The sample consisted of two patients with the same medical diagnosis of inguinal hernia. Samples were selected using purposive sampling based on inclusion and exclusion criteria. Data collection techniques included interviews, physical examinations, and document reviews. Results: The study found that after the implementation of routine deep breathing relaxation therapy for three days, Patient 1’s acute pain was alleviated, with a pain scale reduction from 5 (moderate) to 3 (mild). Patient 2 experienced a reduction from 4 (moderate) to 3 (mild). Additional problems such as anxiety, sleep pattern disturbances, and risk of infection were also resolved. Besides reducing pain, this technique helped decrease anxiety and improve patient comfort. Conclusion: Deep breathing relaxation therapy is an effective and safe non-pharmacological nursing intervention to reduce acute pain in hernia patients. This technique is recommended as a complementary approach in nursing pain management in hospital settings.